Pengaruh Penerapan Ta’zir dalam Meningkatkan Kedisiplinan Santri di Pondok Pesantren Nurul Huda Banat Simbang Kulon Buaran Pekalongan - Fathatur Rizqiyah (ISLAMIKA, 2021)
This study discusses the efforts of the Islamic boarding school in dealing with deviant behavior in students at the Nurul Huda Banat Islamic boarding school Simbang Kulon Buaran Pekalongan. This research is motivated by the problem of deviant behavior carried out by students at the Nurul Huda Banat Islamic boarding school. Deviant behavior with violations of the rules and regulations set by the pesantren. Pesantren has a very important role in building morale in students and has a very important role in overcoming deviations committed by students. This study aims to determine how the influence of ta'zir on the discipline of students, this study uses a qualitative approach and case study methods. Data was collected by using interview, observation, and documentation techniques. The research information consisted of the boarding school administrator and one of the female students of the Nurul Huda Banat Islamic boarding school. It is hoped that the existence of ta'zir can foster a disciplined attitude in students.